Population Growth: Challenges In The Fulfillment of The Right To Work - Tan, Winsherly; Situmeang, Ampuan; Jaya, Febri (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Population growth has positive and negative impacts on a region. Batam city is a city with a fairly large population and Batam City must be able to fulfill its citizens' rights.Purposes of the Research: This study aims to analyze the fulfillment of the right to work and identify ways to control the rate of population growth to meet the need for jobs. Methods of the Research: The method used in this research is normative juridical. The study used is library research. The basis used in this study is the juridical basis which consists of the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights and the theoretical basis used is the legal system theory of Lawrence Meir Friedman. Results of the Research: Based on the results of the study, it was found that the population growth in the Batam city is increasing and the Batam city has an obligation to fulfill the right to work for its residents. Therefore, Batam City must make a population grand design which also contains strategic plans for managing human resources and strategies for preparing jobs for its residents